Frequency of gall bladder metaplasia and its distribution in different regions of gall bladder in routine cholecystectomy specimens - Sharma, Renu; Chander, Bal; Kaul, Rashmi; Rattan, Amit; Sood, Atal; Sharad, Kavita; Khajuria, Meenakshi (International Journal of Research in Medical Sciences, 2017)
Background: In India, gall stone disease is more common in women in the north, north east and east as compared to other zones in the country. Gall bladder metaplasia has been documented as the precursor lesion of dysplasia and therefore carcinoma. Present study was conducted to ascertain the frequency and type of metaplasia along with distribution in different regions of gall bladder. Methods: All the post cholecystectomy gallbladder samples submitted for histopathology comprised the study material. Three sections were from body, fundus, and neck each. The five microns thick paraffin sections were cut with microtome and stained with Hemotoxylin and Eosin (H and E). Results: The present study was conducted on 119 cholecystectomy specimens submitted for histopathological examination. Amongst premalignant lesions, cholecystitis with metaplasia was seen in 55 (46.2%) cases. Pyloric metaplasia without intestinal metaplasia was most common metaplasia (30.2%) followed by combined metaplasia (12.60%) and only intestinal metaplasia (3.36%). Out of 55 cases, fundus showed metaplasia in 47 followed by body (44) and neck (36). Conclusions: Very high frequency of metaplasias was observed (46.2%) in routine cholecystectomy specimen with pyloric metaplasia as the predominant type and intestinal metaplasia was accompanied with pyloric metaplasia in most of the cases. Metaplasia was found to be more or less equally distributed in different regions of gall bladder.